Analysis of Food and Non-Food Consumption Patterns Household - Firmansyah Putra; Munajat Munajat; Yetty Oktarina; Novegya Ratih Primandari (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study aims to determine the influence of household income, head of household education level, and number of family members on consumption patterns in Ogan Komering Ulu Regency. Methodology: The study uses quantitative descriptive analysis with multiple linear regression analysis tools. Results: The findings show that household consumption is influenced not only by regional typology but also by socioeconomic conditions. Multiple linear regression analysis reveals that household income, head of household education level, and number of family members positively correlate with food and non-food consumption patterns in Ogan Komering Ulu Regency. Findings: Hypothesis testing indicates that household income significantly affects food and non-food consumption patterns. The education level of the head of household also significantly affects both food and non-food consumption patterns. However, the number of family members significantly affects food consumption patterns but does not significantly affect non-food consumption patterns. Novelty: This research provides insights into how socioeconomic factors influence consumption patterns in a specific region. Originality: The study offers a detailed analysis of the relationship between household socioeconomic characteristics and consumption patterns. Conclusions: Household income and head of household education level significantly influence both food and non-food consumption patterns, while the number of family members significantly influences only food consumption patterns. Type of Paper: Empirical Research Article Keywords: Consumption Patterns, Food, Non-Food, Household